Biological and mineralogical controls over cycling of low molecular weight organic compounds along a soil chronosequence. (June 2019) - McFarland, Jack W.; Waldrop, Mark P.; Strawn, Daniel G.; Creamer, Courtney A.; Lawrence, Corey R.; Haw, Monica P.
Abstract: Low molecular weight organic compounds (LMWOC) represent a small but critical component of soil organic matter (SOM) for microbial growth and metabolism. The fate of these compounds is largely under microbial control, yet outside the cell, intrinsic soil properties can also significantly influence their turnover and retention. Using a chronosequence representing 1200 ka of pedogenic development, we compared physicochemical vs biological controls on the turnover and retention of fast-cycling carbon (C), e.g. glucose (GLU) and p -hydroxybenzoic acid (PHBA). Along the chronosequence, we observed mineralogical gradients whereby amorphous constituents were greatest in intermediate-aged sites, while older sites demonstrated soils with more ordered and less reactive mineralogy. Soil microbial community composition varied along the soil chronosequence and we observed reductions in total biomass and fungal biomass from younger to older sites, but this did not affect the turnover of LMWOC. Microbial utilization of LMWOC was substrate- and soil-dependent; amorphous Fe and Al oxides reduced the respiration of PHBA but respiration from glucose remained less affected. Variation in soil mineralogy did not significantly alter recovery of PHBA within microbial biomass or fungal vs. bacterial biomarkers, suggesting that reduced respiration of the phenolic resulted from direct mineral interaction with ionizable functional groups rather than changes to microbial allocation of PHBA. We conclude patterns of soil carbon storage observed across chronosequences are moderated by mineralogical effects on microbial access to LMWOC, independent of variation in microbial community composition. Graphical abstract: Along the Cowlitz River soil chronosequence (∼1200 ka ) clear chronological transformations in mineralogical (e.g., pedogenic Fe and Al) and textural properties result in a gradient of surface soils with comparatively higher abundance of amorphous constituents (active Fe and Al) among intermediate-aged sites, and more ordered and less reactive mineralogy (crystalline Fe oxide) among older sites. Soil microbial community composition varied (depicted as different color and constituency in the graphic) with soil mineralogy and texture, but this had little effect on the turnover of low molecular weight organic compounds (LMWOC). Patterns of soil carbon (C) storage observed across the chronosequence are moderated by mineralogical effects on microbial access to LMWOC, independent of variation in microbial community composition. Metabolization of glucose to CO2 was low (high C assimilation efficiency) regardless of edaphic properties. In contrast, p -hydroxybenzoic acid, a substrate with variable charge capacity, and typically lower C assimilation efficiency, demonstrated reduced metabolization to CO2 among soils with higher active Fe and Al. Presumably this is due to direct mineral interaction with ionizable functional groups as opposed to variation in microbial allocation of p -hydroxybenzoic acid.Image 1 Highlights: The Cowlitz River soil chronosequence represents 1200 ka of pedogenic development. We examined relationships between soil mineralogy, microbes, and rates of C turnover. Microbial community composition, but not functionality varies with soil age. Soil mineralogy (especially Al and Fe chemistry) moderates microbial access to LMWOC. Internal allocation of LMWOC to microbial products drives short-term C retention.